Hepatic Dysfunction during Induction Chemotherapy in Children with Acute Lymphoblastic Leukemia and Lymphoblastic Lymphoma and Its Effects on Subsequent Therapy and Outcome - Reddy, Nalla Anuraag; Raj, Keerthi; Lashkari, Harsha Prasada (Indian Journal of Medical and Paediatric Oncology, 2024)
Introduction The overall survival rate for childhood acute lymphoblastic leukemia (ALL) and lymphoblastic lymphoma (LBL) has shown tremendous growth in the recent years. Hepatic dysfunction is one of the complications seen during therapy and can add to the underlying morbidity of the disease, delay in chemotherapy, modification of drugs, and rarely fulminant hepatic failure.Objective This article aims to find out the prevalence of hepatic dysfunction during induction chemotherapy for ALL and LBL.Materials and Methods This was a retrospective study, where the data of all children between 1 and 18 years of age with ALL and LBL treated at our center as per the UK-ALL 2003 protocol between December 2013 and December 2021 have been included from the medical records. Hepatic dysfunction was defined as grade 3 and 4 alanine transaminase (ALT) and aspartate transaminase (AST) levels as per Common Terminology Criteria for Adverse Events v5.0 and hyperbilirubinemia as ≥ 1.4 mg/dL as the chemotherapy modification begins at this cutoff. Data from children with hepatic dysfunction was compared with those without hepatic dysfunction using chi-squared test and Student's t-tests. Those variables with a p-value of < 0.2 were analyzed with multivariate regression analysis. Kaplan–Meier survival estimates were used to calculate the event-free survival (EFS).Results A total of 142 children were included in the study. Thirty-one (21.8%) children developed hepatic dysfunction, 14 (9.9%) of them with ALT/AST elevation and 27 (19%) with bilirubin elevation. Weight (mean 25 ± 13.5, p 0.01), body surface area (mean 0.87 ± 0.29, p 0.02), and National Cancer Institute high risk (p 0.005) were associated with hepatic dysfunction in univariate analysis but none of them were significant in multivariate regression analysis. Treatment modification was required in 14/31 children with hepatic dysfunction. Death in induction was more among children with hepatic dysfunction (p < 0.001). There was no significant impact on minimal residual disease outcomes. Five-year EFS (death or relapse) was 59.93 ± 9% in children with hepatic dysfunction as opposed to 72 ± 5.0% in those without hepatic dysfunction (95% confidence interval, p = 0.07).Conclusion One in five children with ALL and LBL on induction therapy developed hepatic dysfunction. Almost half of those with hepatic dysfunction required chemotherapy modifications.
Keywords: acute lymphoblastic leukemia; lymphoblastic lymphoma; hyperbilirubinemia; chemotherapy